ROLE OF NATRIUM-URETIC PEPTIDES IN THE DIAGNOSTICS OF HEART FAILURE - I. A. Sharoshina; B. A. Sidorenko; D. V. Preobrazhensky (Российский кардиологический журнал)
Role of natrium-uretic peptides in the diagnostics of heart failure.